Spotted Fever: Epidemiology and Vector-Rickettsia-Host Relationship in Rio de Janeiro State - Montenegro, Diego C.; Bitencourth, Karla; de Oliveira, Stefan V.; Borsoi, Ana P.; Cardoso, Karen M.; Sousa, Maria S. B.; Giordano-Dias, Cristina; Amorim, Marinete; Serra-Freire, Nicolau M.; Gazêta, Gilberto S.; Brazil, Reginaldo P. (Frontiers in Microbiology, 2017)
The eco-epidemiological scenario of spotted fever (SF), a tick-borne disease that affects humans and other animals in several countries around the world, was analyzed in Rio de Janeiro State, Brazil. During the last 34 years, 990 SF cases were reported in Rio de Janeiro State (the Brazilian state with the highest population density), including 116 cases confirmed by serology (RIFI) or PCR, among 42.39% of the municipalities with reported cases of SF. The epidemiologic dynamics of SF in RJ State are very heterogeneous in time and space, with outbreaks, high mortality rates and periods of epidemiological silence (no SF cases reported). Furthermore, it exhibited a changing epidemiological profile from being rural to becoming an urban disease. This study identified arthropods infected with Rickettsia felis, R. bellii and R. rickettsii, and found that the abundance of ectoparasites was associated with specific hosts. The R. rickettsii-vector-host relationship was most evident in species-specific parasitism. This suggests that the association between dogs, cattle, horses, capybaras and their main ectoparasites, Rhipicephalus sanguineus and Ctenocephalides felis, Rhipicephalus microplus, Dermacentor nitens, and Amblyomma dubitatum, respectively, has a key role in the dynamics of R. rickettsii transmission in enzootic cycles and the maintenance of carrier ectoparasites, thus facilitating the existence of endemic areas with the ability to produce epidemic outbreaks of SF in RJ. This study found confirmed human infections for only the R. rickettsii carrier Amblyomma sculptum, which reinforces the importance of this species as a vector of the pathogen in Brazil. This study can be adapted to different eco-epidemiological scenarios of spotted fever throughout the Americas.